(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Economic polarization, characterized by widening income disparities, poses significant challenges to fostering entrepreneurial mindsets among youth in developing regions. This study investigates how economic polarization influences the entrepreneurial mindset of youth in Ugep, Cross River State, Nigeria, a region marked by socioeconomic inequalities. Using a descriptive survey design, primary data were collected through structured questionnaires from 300 youths aged 18–35, selected via stratified random sampling. The study employed the Theory of Planned Behavior to assess entrepreneurial intention, self-efficacy, and perceived behavioral control. Findings reveal that economic polarization significantly hampers entrepreneurial mindset development, with 62% of respondents citing limited access to financial resources as a primary barrier. Youth from lower-income brackets exhibited lower entrepreneurial self-efficacy (M = 2.8, SD = 0.7) compared to their higher-income counterparts (M = 3.5, SD = 0.6). Regression analysis indicated that economic disparity negatively predicts entrepreneurial intention (β = -0.42, p < 0.01). The study underscores the need for targeted interventions, such as accessible microfinance and entrepreneurship education, to bridge economic divides and foster entrepreneurial aspirations. Recommendations include policy reforms to enhance financial inclusion and localized training programs to empower disadvantaged youth. This research contributes to understanding the socioeconomic dynamics shaping entrepreneurial ecosystems in rural Nigeria.